Bedouin and 'Abbāsid cultural identities - Khan, Ruqayya Yasmine, author.
1 online resource.
Keywords: "This literary-historical book draws out and sheds light upon the mechanisms of 'the ideological work' that the Arabic Majnūn Laylā story performed for 'Abbāsid urbanite, imperial audiences in the wake of the disappearance of the 'bedouin cosmos.' The study focuses upon the processes of primitivizing Majnūn in the romance of Majnūn Laylā as part of the paradigm shift that occurred in the 'Abbāsid empire after the Graeco-Arabian intellectual revolution. Moreover, this book demonstrates how gender and sexuality are employed in the processes of primitivizing Majnūn. As markers of 'strangeness' and 'foreignness' in the 'Abbāsid interrogations of the multiple categories of ethnicity, culture, identity, religion and language present in their cosmopolitan milieus. Such 'cultural work' is performed through the ideological uses of alterity given its mechanisms of distancing (e.g., temporal and spatial) and nearness (e.g. affective). Lastly, the Majnūn Laylā love story demonstrates, in its text and reception, that a Greco-Arabian and Greco-Persian sub-culture thrived in the centers of 'Abbāsid Baghdad that molded and shaped the ways in which this love story was compiled, received and performed. Offering a corrective to the prevailing views expressed in Western scholarly writings on the Greco-Arabian encounter, this book is a major contribution to scholars and students interested in Arabic and comparative literature, Middle East and Gender Studies"--